STUDI KASUS LINGUISTIK FORENSIK: HOAKS REKAMAN SUARA YANG DIDUGA GATOT NURMANTYO - Saputro, Ghozali (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2019)
(Title: A Forensic Linguistic Study Case: Hoax of Recorded Voice Who Was Allegedly From Gatot Nurmantyo). This study aimed to describe the comparison between languages on Gatot Nurmantyo's Similar Voice Sample (SVS) recording with language on Gatot Nurmantyo's Original Voice Sample (OVS) recordings. The data source were one SVS record and three OVS records (OVS01